Development of an efficient Tef-1α RNA hairpin structure to efficient management of Lasiodiplodia theobromae and Neofusicoccum parvum - Omid Nili (Nature Portfolio, 2021)
Abstract Lasiodiplodia theobromae and Neofusicoccum parvum are serious worldwide-distributed plant pathogenic fungi with a wide host range in tropical and temperate climates. They cause fruit rot, canker, and dieback of twigs in various woody plants. Protection of pruning wounds using fungicides is the prevalent strategy for the management of the diseases caused by these fungi. Chemical control of plant diseases is not environmentally safe and the residues of fungicides are a threat to nature. Furthermore, genetic resources of resistance to plant diseases in woody plants are limited. The aim of this study was to investigate the efficiency of RNA silencing using an efficient hairpin structure based on Tef-1α gene for the management of L. theobromae and N. parvum. Hairpin structure of Tef-1α was cloned in pFGC5941 binary vector and the recombinant construct was named pFGC-TEF-d. Transient expression of pFGC-TEF-d using Agrobacterium LBA4404 in grapevine (Bidaneh Sefid cv.) and strawberry cultivars (Camarosa and Ventana) led to a reduction in disease progress of L. theobromae. The disease reduction in grapevine was estimated by 55% and in strawberries cultivars Camarosa and Ventana by 58% and 93%, respectively. Further analysis of transient expression of pFGC-TEF-d in strawberry (Camarosa) shown disease reduction using Neofusicoccum parvum. Here we introduce RNAi silencing using pFGC-TEF-d construct as an efficient strategy to the management of L. theobromae and N. parvum for the first time.